2020
DOI: 10.1017/ehs.2020.27
|View full text |Cite
|
Sign up to set email alerts
|

Cultural evolution of football tactics: strategic social learning in managers’ choice of formation

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…Our results agree with the analysis of Mesoudi (2020) which observed that the 4.2-3.1 was the most frequent TF in the top five European leagues, followed by 4.3.3 and 4.4.2 TFs. In line with our findings, this study also observed a descending trend of the 4.2-3.1 TF over the years, while the 4-4-2 TF and especially the 4.3.3 TF increased.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results agree with the analysis of Mesoudi (2020) which observed that the 4.2-3.1 was the most frequent TF in the top five European leagues, followed by 4.3.3 and 4.4.2 TFs. In line with our findings, this study also observed a descending trend of the 4.2-3.1 TF over the years, while the 4-4-2 TF and especially the 4.3.3 TF increased.…”
Section: Discussionsupporting
confidence: 92%
“…For this specific case, the 4.2-3-1 can be considered a variant of the 4.5.1. However, it is crucial for the study to consider that the use of the 4.2-3.1 formation is more frequent than the 4.5.1 itself, as well as this TF is one of the most used in the five top European leagues ( Mesoudi, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our model complements other recent work on measuring the strength of transmission biases in cultural datasets of competitive activities, such as the studies by Beheim et al [9] on Go, Miu et al [49] on programming contests and Mesoudi [50] on football strategy. Beheim et al [9] employed multilevel logistic regression to study social and individual learning involved in the board game Go.…”
Section: Discussionmentioning
confidence: 55%
“…It is crucial to mention that the different subspaces of the SDO must be adapted depending on the competition format (7-a-side vs. 11-a-side) and tactical formation. Figure 3 shows the different subspaces according to the most used defensive tactical formations both in 7-a-side and 11-a-side [ 46 , 47 , 48 ]. In addition to the invasive space, the “defensive pressure” is the other dimension related to opponent interaction that reflects the closeness and behavior of defensive players in relation to the attacker with the ball when receiving the ball possession.…”
Section: Methodsmentioning
confidence: 99%